Wild Arbutus unedo L. and Rubus ulmifolius Schott fruits are underutilized sources of valuable bioactive compounds with antioxidant capacity. (17th October 2014) - Ruiz-Rodríguez, Brígida María; Sánchez-Moreno, Concepción; De Ancos, Begoña; Cortes Sánchez-Mata, María de; Fernández-Ruiz, Virginia; Cámara, Montaña; Tardío, Javier
Abstract : Introduction . Several studies reveal the important role played by 'lesser-known' wild fruits since they contain nutritional and functional compounds which have biological properties.Materials and methods . Our work studied the presence of bioactive compounds such as vitamin C (ascorbic acid and dehydroascorbic acid), total phenolic content, phenolic acids, flavonols, anthocyanins and the antioxidant capacity (FRAP, ABTS+ and DPPH in vitro tests) in wild fruits of Arbutus unedo L. and Rubus ulmifolius Schott of Spanish origin, including samples from different seasons and locations.Results and discussion . A wide variability was found in the composition of fruits of the same species, which substantiates the importance of analyzing several batches of wild fruits, to achieve representative results, taking into account the natural variability. Arbustus unedo fruits showed higher vitamin C, mainly in the ascorbic acid form, and phenolic content than R. ulmifolius [(172–419) mg ascorbic acid×100 g–1 fw vs . (5.99–26.83) mg ascorbic acid×100 g–1 fw, and (773–1621) mg total phenolic compounds×100 g–1 fw vs. (376–1326) mg total phenolic compounds×100 g–1 fw, respectively]; phenolic acids and anthocyanins are the major groups of phenolic compounds found in both species, with gallic acid and cyanidin 3-glucoside as the main compounds. Arbustus unedo fruits showed significantly higher Folin-Ciocalteu values than those of R. ulmifolius . These values are higher than those reported for the majority of berries. The significant correlations found among different antioxidant compounds ( r > 0.6300, P < 0.001) may reveal a protective effect between ascorbic acid and phenolic acids or anthocyanins in the fruits. Therefore, Arbutus unedo and R. ulmifolius fruits should be considered as new important sources of safe antioxidants.